The effect of using same language subtitling (SLS) in content comprehension and vocabulary acquisition in Arabic as a foreign language (AFL) - Selim, Aysha Abdel-Moneim (AUC Knowledge Fountain, 2011)
This study investigates the effects of SLS (Same-Language subtitling) on content comprehension and vocabulary acquisition of MSA (Modern Standard Arabic) as L2 at the intermediate level and addresses three research questions: (1) Does SLS enhance or hinder L2 content comprehension when the writing script of L2 is different than that of L1? (2) Does SLS enhance or hinder L2 vocabulary acquisition when the writing script of L2 is different than that of L1? (3) What is students' attitude towards the use of SLS? Twenty seven students of AUC's ALI program with English as L1 were chosen for the study and divided between a control group (without SLS) and a treatment group (with SLS). Instructions concerning the procedure were given in L1 to rule out any false results due to task misinterpretation. Both groups watched an authentic 3:11 minute documentary twice after completing an individual background questionnaire and taking a multiple choice vocabulary pre-viewing test. Post-viewing, participants took the same vocabulary test, then wrote a summary in L1 based on their notes taken during/and in-between the viewings and completed a questionnaire/questions related to their experience with and -/out captions. L1 summaries were analyzed in terms of 23 semantic units related to content comprehension. The degree of vocabulary acquisition was calculated by comparing the responses between the pre- and post-viewing vocabulary multiply choice tests. Results using t-test and one way ANOVA indicate that SLS neither facilitates nor hinders comprehension and vocabulary acquisition. The majority of students enjoyed captions and wanted to continue using them in class. Pedagogical suggestions and future research recommended training with captions and focus on other text- aids, e.g. reverse subtitling at other proficiency levels. Contains 84 references, 17 figures, 5 pictures and 5 tables.